Rig Rates and Drilling Speed: Reinforcing Effects - Petter Osmundsen; Kristin Helen Roll (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper studies how drilling costs are affected by the business cycle. We decompose the major elements in these costs – rig rates and drilling speed –- and examine how they interact with variations in oil prices. A highly relevant consideration in the current circumstances is whether oil companies can compensate for falling oil prices not only by driving down rig rates but also by stepping up drilling speeds. By constructing an econometric model for producing estimates, we find that both high rig rates and reduced drilling productivity will contribute to raising the cost of drilling in boom times, while the reverse is true when oil prices fall. This is good news for an oil industry under challenge. At the same time, the reinforcing effects of two major drilling cost components can explain some of the substantial cyclicality which characterises the oil industry.
Keywords: C51; D24; E32; 330; drilling speed; rig rates; business cycle